Analysis of The Influence of Information Availability, Economic Factors and Changing Trends on Travel Agent Business Sustainability in Digital Era - Ardiyanto Maksimilianus Gai; Afdhal Chatra; Mozart Malik Ibrahim; Samuel PD Anantadjaya; Irma M Nawangwulan (SEULANGA SYSTEM PUBLISHER, 2024)
The goal of this study is to identify key factors in travel agent management and then differentiate their impact on the value creation of these companies. Researchers group methodologies for analyzing value creation in travel agencies into several main categories. The methods are interview and economic-financial analysis. Then we identify value creation indicators to determine economic value-added options, then we conduct empirical contrast. The research results reveal that travel agents, acting as intermediaries, have become highly relevant, absorbing nearly all industries of this sector's production. The historical analysis concludes that travel agents underwent a positive evolution in value creation during the studied period. The revolution in information technology, which increased staff productivity, and the process of sector concentration and association, which increased rotation, are the main factors driving this evolution. Investments in financial assets, tangible assets, and intangible assets also play an important role in transforming the sector's productive structure. While the evolution of margins plays a less significant role in value creation, the sector faces challenges due to price wars and strong competition. The positive impact of the sector's debt also increased, contributing to a significant increase in economic value-added. Finally, travel agents need to pay attention to these factors in their management in order to remain competitive and achieve their ultimate goal of creating value in this sector.